THE ROLE OF ENGLISH LANGUAGE SKILLS IN AGRICULTURAL TECHNOLOGY TRANSFER: A STUDY OF FARMERS AND EXTENSION AGENTS IN IMPROVING RICE SELF-SUFFICIENCY IN LABUHANBATU SELATAN - Hajar Affiah; Durahman Marpaung; Inda Arfa Syera (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research aims to analyze the extent to which English language proficiency influences the success of agricultural technology transfer in Labuhanbatu Selatan Regency, and how this supports increased rice productivity and local food security. The research also aims to identify barriers and formulate strategies for strengthening English language capacity among farmers and extension workers. This research was used a mixed-methods approach, combining qualitative and quantitative methods with survey and observation designs. The qualitative method was conducted using the NVivo application to determine the most frequently occurring words in the data word frequency search, displaying data analysis in the form of tables, Hierarchy Charts, Mind Maps, and Hierarchy Chart Project Maps. The quantitative method used SPSS through classical assumption test, multiple linear regression, and hypothesis testing. Data was collected through interviews and the distribution of questionnaires to 215 respondents, consisting of rice farmers and agricultural extension workers, which was calculated using Slovin's formula, resulting in a research sample of 140 people. The results of this study indicate that English language proficiency has a significant influence on the transfer of agricultural technology. Quantitative findings show that 90.4% of the variation in technology transfer can be explained by English language proficiency, while qualitative results highlight the constraints of understanding technical terms and the role of extension workers as mediators in transferring new agricultural technologies to farmers. As for the relationship between the two, it shows that improving English language skills is a key strategy in accelerating the adoption of agricultural technology to support increased rice self-sufficiency in Labuhanbatu Selatan Regency.